2018
DOI: 10.1371/journal.pone.0194524
|View full text |Cite
|
Sign up to set email alerts
|

Automatic early warning of tail biting in pigs: 3D cameras can detect lowered tail posture before an outbreak

Abstract: Tail biting is a major welfare and economic problem for indoor pig producers worldwide. Low tail posture is an early warning sign which could reduce tail biting unpredictability. Taking a precision livestock farming approach, we used Time-of-flight 3D cameras, processing data with machine vision algorithms, to automate the measurement of pig tail posture. Validation of the 3D algorithm found an accuracy of 73.9% at detecting low vs. not low tails (Sensitivity 88.4%, Specificity 66.8%). Twenty-three groups of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 32 publications
2
90
0
3
Order By: Relevance
“…However, Grant (2004) has previously shown that calves and lambs raise their tails while they suck, and qualitative observations have shown that tame sheep raise their tails while being stroked by humans. Reimert et al (2013), Futro et al (2018) e Larsen et al (2018) suggest that tail movements, in general, may be a good behavioral indicator for positive emotions in pigs. The authors found that the tail movement and the large number of changes in their position were observed more frequently during positive and rewarding events as compared to negative events.…”
Section: Ear Postures As Body Expressionmentioning
confidence: 99%
“…However, Grant (2004) has previously shown that calves and lambs raise their tails while they suck, and qualitative observations have shown that tame sheep raise their tails while being stroked by humans. Reimert et al (2013), Futro et al (2018) e Larsen et al (2018) suggest that tail movements, in general, may be a good behavioral indicator for positive emotions in pigs. The authors found that the tail movement and the large number of changes in their position were observed more frequently during positive and rewarding events as compared to negative events.…”
Section: Ear Postures As Body Expressionmentioning
confidence: 99%
“…In particular, 3D imaging is a technology that is widely deployed in several sectors. In livestock, the deployment of the technology based on 3D digital imaging is in its infancy and the few papers on this topic testify to the cutting edge research exploring this new frontier of PLF (Konsgro, 2014;D'eath et al, 2018). This paper describes an innovative and technological method that was explored to assess the potential of the integration of RFID for animal identification with 3D images of the real bull for the evaluation of the Charolaise breeding bull.…”
Section: Computer Sciencementioning
confidence: 99%
“…Alguns autores Sandem e Braastad, 2005;Reefmann et al, 2009ª; Wemelsfelder et al, 2001;Reefmann et al, 2009ª;All e Terms, 2013;Stellato et al, 2017;Oliveira e Keeling, 2018;Futro et al, 2018;Larsen et al, 2018;Wallgren et al, 2019) foram publicadas com o objetivo de relacionar a movimentação da cauda, como uma área corporal, com a expressão de emoção frente a diferentes situações, em várias espécies.…”
Section: Alterações Corporais Para Detecção De Emoçõesunclassified
“…Os comportamentos de medo em filhotes de cães, foram estudados por (Reefmann et al, 2009;Futro et al, 2018;Larsen et al, 2018;Wallgren et al, 2019) Alguns autores Müller, 2015;Barros et al, 2017;Lu et al, 2017;Amelia et al, 2018;Kopaczka et al, 2018) As características de dor comprometeram 5 áreas na face dos bovinos:…”
Section: Alterações Corporais Para Detecção De Emoçõesunclassified
See 1 more Smart Citation